Clinic-Pathological Aspects of Spleen Hemophagocytic Histiocytic Sarcoma in a Dog - Vieira, Thaynan Cunha; Telles, Luiz Flávio; Nakagaki, Karen Yumi Ribeiro; Cassali, Geovanni Dantas (Acta Scientiae Veterinariae, 2021)
Background: Histiocytes are cells that differentiate into macrophages and dendritic cell lines from bone marrow CD34+ stem cells. The hemophagocytic histiocytic sarcoma (HHS) is the only malignant neoplasm originating from macrophage lineages, being a variation of histiocytic sarcoma (HS), originated from dendritic cells. In general, the HHS shows aggressive biological behavior, due to the erythrophagocytosis characteristic of this disease and overall average survival around seven weeks, affecting mainly Bernese Mountain Dog, Rottweiler and Golden Retriever breeds. Therefore, the objective of this work is to report the case of a dog with HHS, emphasizing the clinical aspects and its diagnostic method. Case: An 8-year-old bitch Rottweiler, was attended with history of inappetence and prostration. The complete blood count showed normochromic normocytic anemia, monocytosis and thrombocytopenia, with serum urea levels below the reference value for the specie in the biochemical examination. The abdominal ultrasound highlighted splenomegaly, with heterogeneous parenchyma and presence of a vascularized mass and an enlarged splenic vein. Thoracic radiographic examination showed multifocal and rounded radiopaque structures in the pulmonary parenchyma, suggesting metastatic formation. Rapid serological tests for detection of the main hemoparasitosis antibodies were negative, as well as negative Coombs test. The animal was submitted to exploratory laparotomy with medial line access and posterior splenectomy. The spleen microscopic evaluation revealed neoplastic proliferation cells in mantle arrangement and solid nests areas, supported by a fine fibrovascular stroma. The cells had broad and eosinophilic cytoplasm, round nuclei and some pleomorphism, rude chromatin and evident nucleoli. It was also observed the presence of marked anisocytosis and anisocariosis, hemophagocytic activity, and 27 mitoses in 10 fields (40 x). There were atypical mitoses and necrosis and extensive hemorrhaged areas. These histopathological findings suggested a histiocytic malignant neoplasia and immunohistochemical analysis was performed to define a better histiocytic neoplasm origin. The neoplastic cells showed positive imunostaining for CD11d and Iba1 and negative imunostaining for CD3 and CD20, as well as a proliferative index of 80%, supporting the diagnosis of HHS in the animal’s spleen. The following hematological analyzes demonstrated persistence of anemia, worsening of thrombocytopenia, prolongation of activated partial thromboplastin time, hypoproteinemia with hypoalbuminemia, serum increase of creatinine, alkaline phosphatase and total bilirubin. Myelogram showed erythrocyte and granulocytic lineage hypoplasia, thrombocytic aplasia and more than 50% of macrophages in bone marrow cell population. The animal’s clinical condition worsened rapidly, after successive transfusions and administration of chemotherapy with lomustine, leading to death 14 days after the surgery. Discussion: HHS is the most serious clinical presentation among histiocytic disorders, conferring an extremely unfavorable prognosis. In addition, the scientific literature that specifically addresses the HHS is rare, with therapeutic extrapolations being performed for the treatment of HS from dendritic cells. The racial predisposition and clinical findings, associated with hematological changes, histopathological analysis and confirmation by immunohistochemistry allowed the diagnosis of HHS, a rare and underreported neoplasm, with aggressive biological behavior and with still inefficient treatment in veterinary medicine.